2015
DOI: 10.1016/j.ijporl.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Consonant discrimination by Mandarin-speaking children with prelingual hearing impairment

Abstract: Consonant discrimination performance of children with profound HI was poorer than those with moderate to severe HI. The ability to discriminate consonant pairs seems to depend on age of acquisition of the consonants. Although the age of first HA fitting and the duration of HA use were not correlated with consonant discrimination outcomes, this finding does not preclude the importance of early HA fitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 42 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…The minimal pairs that scored one standard deviation lower than the overall mean of the 33 consonant pairs were considered difficult, and those that scored one standard deviation above the overall mean were considered easy. This criterion was used in Zhu et al [ 6 ]. Furthermore, a paired samples t-test with Bonferroni adjustment was conducted to compare the performance of each minimal pair obtained in the quiet and noisy conditions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The minimal pairs that scored one standard deviation lower than the overall mean of the 33 consonant pairs were considered difficult, and those that scored one standard deviation above the overall mean were considered easy. This criterion was used in Zhu et al [ 6 ]. Furthermore, a paired samples t-test with Bonferroni adjustment was conducted to compare the performance of each minimal pair obtained in the quiet and noisy conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also revealed a significant effect of noise on consonant perception in children with HL [ 6 ] and adults with NH [ 29 ]. The discrimination of fricatives and affricates was an exception.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations